Chondromesenchymal Hamartoma in Ectopic Thyroid Tissue in a Neonate - Agnes Szepesi; Zsolt Juhasz; Anna Kover; Bela Kajtar; Noemi Benedek; Endre Kalman; Tamas Kovesi; Marianna Imre; Peter Vajda (Georg Thieme Verlag KG, 2019)
A full-term male neonate presented with a left sided cervical lump at the level of the thyroid gland. Magnetic resonance imaging (MRI) showed a benign heterogeneous solid mass with lobulated margins. The tumor underwent complete excision. Histology revealed the diagnosis of chondromesenchymal hamartoma in ectopic thyroid tissue.